Comprehensive genomic profiling for patients with chemotherapy‐naïve advanced cancer. Issue 1 (21st November 2020) - Kondo, Tomohiro; Matsubara, Junichi; Quy, Pham Nguyen; Fukuyama, Keita; Nomura, Motoo; Funakoshi, Taro; Doi, Keitaro; Sakamori, Yuichi; Yoshioka, Masahiro; Yokoyama, Akira; Tamaoki, Masashi; Kou, Tadayuki; et al.
Abstract: Comprehensive genomic profiling (CGP) testing by next‐generation sequencing has been introduced into clinical practice as part of precision cancer medicine to select effective targeted therapies. However, whether CGP testing at the time of first‐line chemotherapy could be clinically useful is not clear. We conducted this single‐center, prospective, observational study to investigate the feasibility of CGP testing for chemotherapy‐naïve patients with stage III/IV gastrointestinal cancer, rare cancer, and cancer of unknown primary, using the FoundationOne ® companion diagnostic (F1CDx) assay. The primary outcome was the detection rate of at least one actionable/druggable cancer genomic alteration. Actionable/druggable cancer genomic alterations were determined by the F1CDx report. An institutional molecular tumor board determined the molecular‐based recommended therapies. A total of 197 patients were enrolled from October 2018 to June 2019. CGP success rate was 76.6% (151 of 197 patients), and median turnaround time was 19 days (range: 10‐329 days). Actionable and druggable cancer genomic alterations were reported in 145 (73.6%) and 124 (62.9%) patients, respectively. The highest detection rate of druggable genomic alterations in gastrointestinal cancers was 80% in colorectal cancer (48 of 60 patients). Molecular‐based recommended therapies were determined in 46 patients (23.4%). CGP testing would be a useful tool for the identification of a potentially effective first‐line chemotherapy. Abstract : Comprehensive genomic profiling (CGP) testing by next‐generation sequencing has been introduced into clinical practice as part of precision cancer medicine to select effective targeted therapies; however, whether CGP testing at the time of first‐line chemotherapy could be clinically useful is not clear. We conducted this single‐center, prospective, observational study to investigate the feasibility of CGP testing for chemotherapy‐naïve patients with stage III/IV gastrointestinal cancer, rare cancer, and cancer of unknown primary, using the FoundationOne ® companion diagnostic assay. We found that CGP testing could be feasible in Japanese clinical practice for chemotherapy‐naïve patients with these cancers, and that CGP testing might be a useful tool to identify a potentially effective first‐line treatment, which will lead to the establishment of precision cancer medicine.